Long-term organic farming impact on soil nutrient status and grain yield at the foothill of Himalayas - Singh, Pranjali; Suyal, Deep Chandra; Kumar, Saurabh; Singh, Dhananjay Kumar; Goel, Reeta (Frontiers in Environmental Science, 2024)
This study aimed to document the effects of the long-term organic farming (OF) on soil quality, agronomical parameters, crop productivity, and food grain yield compared to the conventional farming (CF) system. The crop used in this study is chickpea (Cicer arietinum), and the field was located at Pantnagar, India, in the foothills of Himalayas. The organic farming approach involved utilizing a blend of farmyard manure and vermicompost, combined with a biopesticide comprising neem oil and cow urine. Chickpea grain micronutrient analysis was done via atomic absorption spectrophotometry. It was found that the physicochemical properties of soil in the organic plot were improved compared to the conventional counterpart. At the post-harvesting stage, the organically managed field had higher soil organic carbon than the conventional field (OF-0.93± 0.05%, CF-0.75 ± 0.12%), higher available nitrogen (OF-317 ± 11 kg/ha, CF-240 ± 22 kg/ha), and more available phosphorus (OF-37.4 ± 1.3 kg/ha, CF-25.2 ± 2.5 kg/ha). The agronomical parameters of the chickpea crop were better under organic cultivation, with a significantly high nodule number, nodule dry weight, and grains per pod. Hence, the grain yield of the crop was better under organic cultivation, with the yield of 1,048 kg ha−1, whereas it was 896.5 kg ha−1 for conventional cultivation. The Fe and Zn contents of organically produced chickpea grains were almost double of their conventional counterpart. Therefore, organic cultivation led to better soil fertility, chickpea grain yield, and nutrient status of the crop. It will be beneficial for the nutritious and sustainable production of chickpeas in Himalayan regions.